A programmable, rapidly drivable, high-strength hydrogel based on MXene composite silk fabric and its preparation method
By combining MXene composite silk fabric with NIPAM prepolymerization liquid, high-strength, programmable and fast-driven hydrogel materials are obtained, which solves the existing problems of poor mechanical properties of hydrogels and weak deformation driving force, and realizes powerful driving force and remote control light response functions.
Patent Information
- Application Number
- CN202310578560.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-22
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-05-22
AI Technical Summary
The existing stimulus-responsive hydrogels have problems with poor mechanical properties and weak deformation driving force, which limits their further application in the field of smart materials.
By combining the MXene composite silk fabric with N-isopropyl acrylamide (NIPAM) prepolymerization solution, a single layer of MXene sheet was loaded on the surface of the silk fabric using supramolecular interactions, and MXene composite silk fabric/polyN-isopropyl polyacrylamide composite hydrogel was obtained by ultraviolet polymerization.
It realizes high-intensity, programmable and fast-driven hydrogel material. Its excellent mechanical properties and photothermal conversion efficiency give it a strong driving force, can grasp heavy objects with a weight of more than 60 times, and has remotely controlled light response fast driving function.
Smart Images

Figure CN116640327B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a hydrogel composite material, and in particular to a programmable, rapidly drivable, high-strength hydrogel based on MXene composite silk fabric and a preparation method thereof. Background Art
[0002] The development of the big health industry and artificial intelligence has led to the vigorous development of smart materials, but how to improve the intelligence of materials is one of the core issues in this field. Stimuli-responsive hydrogels have received increasing attention due to their good biocompatibility, softness and wettability, and structural / component designability. Stimuli-responsive hydrogels respond to various types of stimuli in the surrounding environment by adjusting their physicochemical properties or structural conformations. According to their characteristics, stimuli-responsive hydrogels can be divided into humidity-responsive, pH-responsive, temperature-responsive, light-responsive, electric-field-responsive, and magnetic-field-responsive types. At present, stimuli-responsive hydrogels can significantly change their volume or shape under various external stimuli. As the most important smart material, they have been widely used in soft robots, artificial muscles, smart valves and other fields.
[0003] At present, relevant literature reports that the bionic anisotropic structure of hydrogels has been explored for complex actuation. For example, poly(N-isopropylacrylamide) hydrogels can swell below their lower critical solution temperature and shrink above their lower critical solution temperature, thereby achieving actuation behavior. However, the natural isotropic structure and high water content of hydrogels lead to relatively simple actuation modes and weak mechanical properties, respectively, which seriously limit the further application of actuated hydrogels. In particular, hydrogels generally have problems such as poor mechanical properties and weak deformation driving force.
[0004] Existing literature reports that the strength of hydrogels can be improved by designing double network structures, sliding ring structures, regularly arranged mesh structures or nanomaterial reinforcements. By combining high-strength natural biomass materials with stimulus-responsive hydrogels, the mechanical properties can also be greatly improved. For example, by introducing protein fibers or cellulose fibers into stimulus-responsive hydrogels, their mechanical properties can be greatly enhanced, but the anisotropic structure of the stimulus-responsive hydrogel will also become complicated. In addition, the preparation method is also relatively complicated, resulting in its low practicality. Therefore, it is necessary to develop a programmable, fast-actuated, high-strength hydrogel based on MXene composite silk fabric and its preparation method. Summary of the invention
[0005] In view of this, the present invention provides a method for preparing a programmable and rapidly drivable high-strength hydrogel based on MXene composite silk fabric, which solves the problems of poor mechanical properties and weak deformation driving force of existing stimulus responsive hydrogels.
[0006] On the one hand, the present invention provides a method for preparing a programmable and rapidly drivable high-strength hydrogel based on MXene composite silk fabric, comprising the following steps:
[0007] S101: immersing the silk fabric in a single-layer MXene dispersion, placing it on a glass sheet and drying it at room temperature, and then placing it in an air drying oven to dry it to obtain a MXene composite silk fabric;
[0008] S102: Add N-isopropylacrylamide, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone and N,N′-methylenebisacrylamide to Laponite lithium magnesium silicate nanoclay dispersion, stir to completely dissolve it to obtain a prepolymer solution, and finally inject the prepolymer solution into a mold filled with MXene composite silk fabric at the bottom and seal it. After UV polymerization and washing, a programmable, rapidly drivable, high-strength hydrogel based on MXene composite silk fabric is obtained.
[0009] Preferably, the amount of N-isopropylacrylamide is 200 mg, the amount of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone is 2 mg, and the amount of N,N′-methylenebisacrylamide is 4 mg.
[0010] Preferably, the concentration of the monolayer MXene dispersion is 5 mg / mL.
[0011] Preferably, the mass fraction of the Laponite lithium magnesium silicate nanoclay dispersion is 1 wt % and the volume is 1 mL.
[0012] On the other hand, the present invention also provides a programmable, rapidly drivable, high-strength hydrogel based on MXene composite silk fabric.
[0013] The present invention provides a method for preparing a programmable and rapidly drivable high-strength hydrogel based on MXene composite silk fabric. Based on supramolecular interaction, a single-layer MXene sheet is firmly loaded on the surface of the silk fabric, and then the silk fabric is embedded in N-isopropylacrylamide (NIPAM) prepolymer solution. The MXene composite silk fabric / poly (N-isopropylacrylamide) composite hydrogel is obtained by ultraviolet polymerization. The method is simple and easy to promote.
[0014] Furthermore, the materials prepared by this method not only have various programmable complex driven anisotropic structures, high photothermal conversion efficiency, and can achieve remote controlled light response rapid driving; and their excellent mechanical properties give them powerful driving force. They have been designed for a variety of bionic devices, have various programmable complex functions, and can grab objects more than 60 times their own weight. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1This is a schematic diagram of the preparation process of a programmable, rapidly drivable, high-strength hydrogel based on MXene composite silk fabric according to Example 1;
[0016] Figure 2 Scanning electron microscopy and EDS-mapping images of silk fabrics before and after loading with MXene;
[0017] Figure 3 a is the X-ray photoelectron spectrum; Figure 3 b is the transmittance of PNIPAM hydrogel, silk fabric, MXene composite silk fabric, and SMAH material;
[0018] Figure 4 The contact angle test diagram of silk fabric before and after loading MXene;
[0019] Figure 5 a and 5b are the stress-strain curves, Young's modulus and elongation at break of silk fabrics cut at different angles, respectively; Figure 5 c and 5d are the stress-strain curve, Young’s modulus and elongation at break of SMAH material, respectively;
[0020] Figure 6 a Schematic diagram representing the definition and shape of the SMAH shear angle as it changes with temperature; Figure 6 b represents the curve of SMAH 45° bending angle changing with temperature; Figure 6 c represents the curve of SMAH 0° bending angle changing with temperature; Figure 6 d represents the shape variation of SMAH cut at different angles with temperature (all scale bars are 5 mm);
[0021] Figure 7 a represents the temperature rise curve of MXene composite silk fabric under near-infrared light of different powers; Figure 7 b represents the infrared thermal image of MXene composite silk fabric under near-infrared light irradiation of different powers; Figure 7 c represents the bending angle variation curve of SMAH 45° under the illumination of surface light source; Figure 7 d represents the bending angle change curve of SMAH under 45° point light source illumination (all scale bars are 5 mm);
[0022] Figure 8 a represents the programmable complex driving process of the SMAH actuator under near-infrared light irradiation (all scale bars are 5 mm); Figure 8 b represents the finite element simulation diagram of the SMAH driving process.
[0023] Fig. 9 a represents the schematic diagram of the anisotropic structure of the SMAH actuator simulating the eagle claw; Fig. 9b represents the schematic diagram of the SMAH grab-and-put process; Fig. 9 c represents a photograph of the SMAH actuator's grasping-putting process; 9d represents a schematic diagram of the anisotropic structure of the SMAH actuator simulating snake hunting; Fig. 9 e represents the schematic diagram of the SMAH bionic snake’s predation process; Fig. 9 f represents the photo of the SMAH bionic snake's predation process;
[0024] Fig.10 a represents the schematic diagram of the anisotropic structure of the SMAH actuator simulating an octopus; 10b represents the schematic diagram of the light-responsive bending and spiral motion of the "octopus leg"; 10c represents the schematic diagram of the light-responsive bending and spiral motion of the "octopus leg" (under 808nm laser, power of 5.0W, spot diameter of 10.0mm); Fig.10 d represents the schematic diagram of the continuous forward crawling of the “octopus” in response to light; Fig.10 e represents the schematic diagram of the continuous forward crawling of the “octopus” in response to light; Fig.10 f represents a schematic diagram of the light response flipping process of the "octopus". DETAILED DESCRIPTION
[0025] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0026] The Laponite lithium magnesium silicate (XLG type) nanoclay, N-isopropylacrylamide (NIPAm), N,N′-methylenebisacrylamide (MBAA), MXene (Ti 3 C 2 Tx, 0.5wt% aqueous solution), 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (I-2959), and poly (N-isopropylacrylamide) (PNIPAM) were purchased from regular manufacturers, and silk fabrics were purchased from Hangzhou Zaiyuan Silk Factory.
[0027] Example 1: A method for preparing a programmable and rapidly drivable high-strength hydrogel based on MXene composite silk fabric, such as Figure 1 , including the following steps:
[0028] S101: The silk fabric was immersed in a 5 mg / mL monolayer MXene dispersion for 10 min, then placed on a glass slide and dried at room temperature for 3 h, and then placed in a 40°C air drying oven for 3 h to obtain a MXene-loaded silk fabric.
[0029] S102: Add 200 mg of N-isopropylacrylamide, 2 mg of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone and 4 mg of N,N′-methylenebisacrylamide to 1 mL of 1 wt% Laponite lithium magnesium silicate nanoclay dispersion, stir to completely dissolve it to obtain a prepolymer solution, and finally inject it into a mold with a 0.2 mm bottom filled with MXene-loaded silk fabric and seal it. Irradiate it under a 6 W ultraviolet lamp for 3 h, and obtain a nested structure smart hydrogel (SMAH) after ultraviolet photopolymerization and washing.
[0030] (1) Scanning electron microscopy test of the MXene-loaded silk fabric prepared in Example 1
[0031] like Figure 2 The results showed that the silk fabric without MXene modification was white, while the silk fabric loaded with MXene was black. Further observation of the image using a scanning electron microscope (SEM) revealed that the surface of the silk fabric without MXene modification was smooth, while the surface of the silk fabric loaded with MXene was rough, indicating that the silk fabric had been successfully loaded with MXene.
[0032] (2) Element scanning (EDS) and X-ray photoelectron spectroscopy tests were performed on the MXene-loaded silk fabric prepared in Example 1
[0033] like Figure 3 The results show that the element scanning (EDS) results show that the Ti content in the silk fabric modified with MXene is much greater than that in the silk fabric not modified with MXene, and the X-ray photoelectron spectroscopy (XPS) test found that the silk fabric modified with MXene showed two peaks, Ti2p and F1s, while the silk fabric not modified with MXene did not have these two peaks, indicating that the loaded MXene and the silk fabric are closely combined. The transmittance of poly N-isopropylacrylamide (PNIPAM) hydrogel, SMAH, MXene-loaded silk fabric and initial silk fabric was further compared. Among them, the transmittance of PNIPAM was the largest and that of SMAH was the smallest, indicating that SMAH has excellent photothermal properties.
[0034] (3) Contact angle test of the smart hydrogel material prepared in Example 1
[0035] like Figure 4The contact angle test results show that the contact angle of silk fabric without MXene loading is greater than 90° at 60s, indicating that silk fabric itself is a hydrophobic material; when silk fabric is loaded with MXene, the contact angle becomes less than 90°, and it is converted into a hydrophilic material. The contact angle of silk fabric loaded with MXene is much smaller than that of silk fabric without MXene loading. Therefore, MXene not only makes silk fabric have better photothermal performance, but also improves its hydrophilicity, making it more closely combined with hydrogel.
[0036] (4) Mechanical properties test of the smart hydrogel material prepared in Example 1
[0037] Cut the silk fabric into two different samples, one at an angle of 0° to the horizontal direction (silk-textiles0°) and the other at an angle of 45° to the horizontal direction (silk-textiles45°). The stress-strain curve is shown in Figure 5 a and 5b. Compared with silk-textiles45°, silk-textiles0° has a higher breaking tensile strength. When we stretch it along the 45° direction, the silk fabric becomes very thin and long. According to the comparison of stress-strain curves of silk fabrics in different directions, it can be known that silk fabrics have anisotropy. Figure 5 c and 5d. The elongation at break of the 45° cut SMAH is longer and the Young's modulus is lower than that of the 90° cut SMAH. This indicates that the smart composite hydrogel prepared in Example 1 has an anisotropic structure.
[0038] (5) Testing the complex deformation performance of the smart hydrogel material prepared in Example 1
[0039] First, the SMAH is precisely programmed to drive by cutting it in different shapes and angles. Figure 6 As shown in a, the SMAH is cut into 15 mm strips at different angles, and the angle between the cutting direction and the parallel direction is recorded as n. Due to the different values of n, the AH actuator can achieve different spiral structures. When n=45, the SMAH actuator can be bent into a circle.
[0040] Secondly, the thermal response of the SMAH actuator in water of different temperatures was tested. Figure 6 As shown in Fig. b, when the cutting angle of the SMAH actuator is 45°, the SMAH actuator bends and deforms. As the temperature increases, the actuator gradually bends. When the temperature is 34°C, the actuator is circular, and as the temperature increases, the bending angle of the actuator increases. In addition, when the cutting angle of the SMAH actuator is 0° or 90°, it can gradually become a spiral structure, and the bending angle increases with the increase of temperature (as shown in Fig. Figure 6 c).
[0041] Finally, in order to explore more diverse three-dimensional complex drives, such as Figure 6 As shown in Figure d, a series of SMAH actuators with precise programs and different cutting angles are designed, including 0°, 15°, 30°, 45°, 60°, 75° and 90°. When the cutting angle increases from 45° to 90°, the SMAH actuator changes from bending to spiral, the pitch increases, and the radius decreases. When the cutting angle decreases from 45° to 0°, the SMAH actuator also changes from bending to spiral, the pitch increases, the radius decreases, but the spiral direction is opposite. This shows that the composite hydrogel prepared in Example 1 can be programmed and driven quickly.
[0042] (6) Study on the photothermal driving behavior of the smart hydrogel material prepared in Example 1
[0043] First, the SMAH actuator was irradiated with NIR at different powers, as shown in 7a and Figure 7 The results show that the enhanced near-infrared power can achieve a faster heating rate, 8.0W / cm 2 and 10.0W / cm 2 The difference between the photothermal curves is small, 8.0W / cm 3 Near-infrared light can also reach the critical transformation temperature of PNIPAM hydrogel in a short time.
[0044] To further investigate the driving speed of the SMAH actuator, one end of the SMAH was fixed at 45° and illuminated with a surface light source to explore its bending behavior ( Figure 7 c). Under irradiation in the near-infrared region, the bending angle of the SMAH actuator can reach about 214° in 3 seconds (average bending speed of 71.3° / s). Illuminated with a point light source to explore its bending behavior ( Figure 7 d). Under near-infrared irradiation, the bending angle reaches about 97° within 3.5s (the average folding speed is 27.7° / s)
[0045] The programmable three-dimensional complex deformation of the MSAH actuator was further explored ( Figure 8 ). At 6.0W / cm 2 Under the irradiation of near-infrared light intensity, when the cutting angle is 45°, SMAH can provide simple bending actuation along the longitudinal direction. When the cutting angle is adjusted from 45° to 0° / 90°, SMAH provides different 3D complex spiral actuation ( Figure 8 a). In contrast to existing stimuli-responsive hydrogel actuators that only provide one or a few specific actuations, this SMAH actuator has more complex programmable actuation under near-infrared light. Therefore, the SMAH actuator of this embodiment 1 provides advanced complex actuation and expands the application of soft smart actuation materials. To confirm the actuation process of the SMAH actuator, the finite element simulation results show excellent consistency, such as Figure 8 As shown in result b, it is further verified that the SMAH actuator can achieve precise photothermal driving and complete complex driving deformation behavior.
[0046] (7) Study on bionic application of SMAH prepared in Example 1
[0047] Based on the advantages of SMAH actuators such as strong driving force and complex driving programmability, we designed various remote-controlled light-responsive bionic actuators ( Fig. 9 and Fig.10 ).
[0048] First, design a four-arm gripper that imitates bird claws, such as Fig. 9 As shown in Figs. a and 9b, a cross-shaped fixture is cut from the SMAH actuator. The length direction of the actuator is 45° to the horizontal direction. The cross section of the fixture is fixed at one end of the cylinder. The "bionic gripper" can pick up objects weighing 60 times its own weight. After the near-infrared irradiation is removed, the actuator can still firmly grasp the object within 5 seconds. The fixture can transfer the target object within the capture time, and the hydrogel gradually expands after 5 seconds to automatically release the object ( Fig. 9 c).
[0049] Using the unique anisotropic structure, high-strength mechanical properties and high driving force of SMAH, a bionic snake actuator was made. This snake-like actuator simulates the snake's predation process ( Fig. 9 d). The special structure of the snake-like device can achieve bending and spiraling in the same actuator directly cut by SMAH, without splicing and bonding, and can simulate the movements of "biting prey" and "retreating" ( Fig. 9 e) When near-infrared irradiation is applied to the "snake mouth" of the actuator (SMAH 45°), the mouth of the snake-like actuator bends due to the photothermal response and then bites the "mouse". When near-infrared irradiation is applied to the "snake body" of the snake-like actuator (SMAH 0°), the snake body spirals upward to achieve a "retreat" movement.
[0050] Secondly, a "bionic octopus" was designed, integrating various complex drives to achieve fast light response ( Fig.10 a). When near-infrared light is irradiated on different "octopus legs", their bending or spiraling motion is controlled individually; when near-infrared light is irradiated on multiple "octopus legs" at the same time, the legs can be controlled to bend and spiral together at the same time ( Fig.10 b and 10c). At the same time, its specially designed terrain allows the "octopus" to crawl forward 3.5 cm ( Fig.10 d and 10e). In addition, due to the uneven irradiation of the near-infrared spot on the "octopus", the "octopus" can achieve rapid flipping motion under local laser irradiation with a power of 15.0 W and a spot diameter of 15.0 mm ( Fig.10 f).
[0051] In another embodiment, non-woven fabric or rice paper is used instead of silk fabric to be compounded with the hydrogel of Example 1, but such excellent mechanical properties and photothermal driven deformation ability cannot be obtained.
[0052] In summary, the present invention provides a programmable complex, powerful and fast anisotropic biomimetic driving hydrogel. Based on supramolecular interactions, a single layer of MXene sheets can be firmly loaded on the surface of silk fabrics, and MXene composite silk fabrics are embedded in N-isopropylacrylamide (NIPAM) precursor solution to obtain the prepared MXene composite silk fabric / poly N-isopropylacrylamide composite hydrogel. The method is simple and easy to promote.
[0053] The material prepared by this method not only has various programmable complex driven anisotropic structures, but also has excellent mechanical properties that give it a strong driving force. In addition, the SMAH hydrogel of the present invention has high photothermal conversion efficiency, can achieve remote controlled light response rapid drive, has been designed for a variety of bionic devices, has various programmable complex functions, is powerful, and can grab heavy objects more than 60 times its own weight.
[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a programmable, fast-actuated, high-strength hydrogel based on MXene composite silk fabric, characterized in that The following steps are involved: S101: immersing the silk fabric in a single-layer MXene dispersion, placing it on a glass sheet and drying it at room temperature, and then placing it in an air drying oven to dry it to obtain a MXene composite silk fabric; S102: Add N-isopropylacrylamide, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone and N,N′-methylenebisacrylamide to Laponite magnesium silicate lithium nanoclay dispersion, stir to completely dissolve to obtain a prepolymer solution, and finally inject the prepolymer solution into a mold filled with MXene composite silk fabric at the bottom to seal, and obtain a programmable, fast-actuated, high-strength hydrogel based on MXene composite silk fabric after UV polymerization and washing; The amount of N-isopropylacrylamide is 200 mg, the amount of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone is 2 mg, and the amount of N,N′-methylenebisacrylamide is 4 mg; The concentration of the monolayer MXene dispersion is 5 mg / mL; The mass fraction of the Laponite lithium magnesium silicate nanoclay dispersion is 1 wt %, and the volume is 1 mL.
2. A programmable, rapidly actuatable, high-strength hydrogel based on MXene composite silk fabric prepared according to the method of claim 1.
Citation Information
Patent Citations
Sericin-based semi-interpenetrating temperature-sensitive nano-composite hydro-gel and preparation method thereof
CN102206351A
Light-driven shape-programmable MXene composite hydrogel driver and preparation method thereof
CN113045716A